Self-Control, Intimate Partner Abuse, and Intimate Partner Victimization: Testing the General Theory of Crime in Thailand - Kerley, Kent R.; Xu, Xiaohe; Sirisunyaluck, Bangon (Deviant behavior, 2008)
Gottfredson and Hirschi's ( 1990 ) treatise on low self-control has been the subject of much debate and empirical testing. Although the theory was developed as an explanation for criminal offending, researchers have examined recently whether low self-control may increase the risk of criminal victimization. This study contributes to the literature by (1) simultaneously assessing the effects of low self-control on offending and victimization, (2) focusing on psychological and physical intimate partner abuse in the family context, and (3) using a cross-cultural dataset. We utilize Tobit regression to test the impact of low self-control on intimate partner aggression and victimization in a sample of 794 married females residing in Bangkok, Thailand. Results provide a more thorough understanding of self-control theory and intimate partner abuse in a cross-cultural context.